PENGARUH MODEL PEMBELAJARAN TAI TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA MATERI UNSUR SENYAWA CAMPURAN - Iqbal, Muhammad; Sahputra, Rachmat; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe purpose of this study were to determine whether there was a significant difference of motivation and learning outcomes  between student who taught using Team Assisted Individualization (TAI) and conventional mode, and determine effect size of TAI model the form of research that will be used was experimental research. Saturated sampling used to select the sample. The essay test and questionnaire about students’ motivation were used as instruments. The posttest results of both class were analyzed using the U-Mann Whitney test with a= 5%. The result showed that the value of  Asymp. Sig (2-tailed) 0.000. It indicated that there was a significant difference between learning outcomes in control and experiment class. The questionnaire about students’ motivation results of both class were analyzed using the U-Mann Whitney test with a= 5%. It also revealed the value of Asymp. Sig (2-tailed) at 0.000. It indicated that there was the ificant sigdifference students’ motivation in control and experiment class. according to calculation using cohens formula, the effect size of TAI learning was 0,7622 which categorized as excellent  Kata kunci: TAI, Unsur, Senyawa dan Campuran, Motivasi, Hasil Belajar.